Dochody gmin i miast na prawach powiatu z podatków lokalnych - Motek, Paweł (Incomes of Communes and Poviat-Ranking Towns from Local Taxes, 2009)
Opinions on the significance of taxes have changed with the development of theories of public finance and tasks of the state. It is assumed that taxes perform four basic functions: fiscal, redistributive, stimulating, and informative-supervisory, with the fiscal function being of primary importance among them. The aim of this paper is to present the significance of local taxes in financing the communes. The analysis covers the years 2005-2007. In 2007 local taxes brought commune budgets a total of 17.5 billion zlotys. Predominant among them was the real estate tax, which contributed 13.3% to the communes'total income and 10.9% to the income of poviat-ranking towns
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 208-215